The User Paradox in Technology Testing - Per Hetland (Universitetsforlaget, 2011)
Technology testing provides arenas for interaction between users and producers. In the experiments potential user needs and user-values regarding new technology are communicated to facilitate invention and diffuse innovation. This article provides a framework for discussing how users contribute to both the knowledge and policy construction processes when participating in technology testing.